1996
DOI: 10.1007/bf02511881
|View full text |Cite
|
Sign up to set email alerts
|

Measuring neighborhood context for young children in an urban area

Abstract: Awareness of worsening conditions in urban areas has led to a growing interest in how neighborhood context affects children. Although the ecological perspective within child development has acknowledged the relevance of community factors, methods of measuring the neighborhood context for children have been quite limited. An approach to measuring neighborhood environments was tested using the average perceptions of caregivers of young children sampled from high‐ and low‐risk block groups. Individual‐ and aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(118 citation statements)
references
References 27 publications
2
111
0
3
Order By: Relevance
“…20 Census block group have been found to be an appropriate proxy for identifying immediate influences on the lives and experiences of local individuals. 21 Details of the neighborhood selection process can be found elsewhere. 18 In brief, we selected all neighborhoods falling within the lowest quartile of wealth in Baltimore City and then used a used a combination of demographic, economic, and violence-related data to sort neighborhoods based on their overall high or low risk for neighborhood violence occurrence.…”
Section: Neighborhood Selectionmentioning
confidence: 99%
“…20 Census block group have been found to be an appropriate proxy for identifying immediate influences on the lives and experiences of local individuals. 21 Details of the neighborhood selection process can be found elsewhere. 18 In brief, we selected all neighborhoods falling within the lowest quartile of wealth in Baltimore City and then used a used a combination of demographic, economic, and violence-related data to sort neighborhoods based on their overall high or low risk for neighborhood violence occurrence.…”
Section: Neighborhood Selectionmentioning
confidence: 99%
“…First, neighborhood features were measured by parent perception, which could lead to under-or overestimating the presence of these supports. However, one study of perceptions of caregivers of young children from high-and low-risk areas found parent-reported perceptions of the neighborhood environment to be reliable (7). Parents' perception of neighborhood features is relevant to adolescent behavior because parents typically decide whether their adolescent, particularly a young adolescent, is allowed to play at the park, walk or bike to school, or use neighborhood…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of other cities have shown similar clustering of social problems and correlations with concentrated poverty. 2,41 While useful as a summary predictor, concentrated disadvantage does not lend insight into the processes that lead to and result from economic disadvantage, the processes that distinguish neighborhoods, including neighborhoods that may suffer relative economic impoverishment, but for different reasons and with different consequences. Taken together, the social stress dimension sheds light on the social problems that accompany concentrated disadvantage.…”
Section: Discussionmentioning
confidence: 99%